The Outcomes and Adverse Drug Patterns of Immunomodulators and Thrombopoietin Receptor Agonists in Primary Immune Thrombocytopenia Egyptian Patients with Hemorrhage Comorbidity - Eman Mostafa Hamed; Ahmed R. N. Ibrahim; Mohamed Hussein Meabed; Ahmed M. Khalaf; Doaa Mohamed El Demerdash; Marwa O. Elgendy; Haitham Saeed; Heba F. Salem; Hoda Rabea (Pharmaceuticals, 2023)
Immune thrombocytopenia (ITP) treatment has evolved recently. However, none of the treatments have only benefits without drawbacks. This study aimed to compare the clinical outcomes and adverse drug patterns of Eltrombopag, Romiplostim, Prednisolone + Azathioprine, High Dose-dexamethasone (HD-DXM) (control group), and Rituximab in primary ITP Egyptian patients. All patients were initiated with corticosteroids, HD-DXM, as a first-line treatment for the first month immediately following diagnosis. Four hundred sixty-seven ITP patients were randomly assigned to five groups. The outcome measures were judged at baseline, at the end of treatment (6 months), and after an additional 6-month free treatment period. The follow-up period for which relapse is noted was 6 months after the end of treatment. Eltrombopag and Romiplostim resulted in a significantly higher incidence of sustained response than Rituximab, HD-DXM, and Prednisolone + Azathioprine (55.2% and 50.6% vs. 29.2%, 29.1%, and 18%, respectively; p-value < 0.001). More patients on immunomodulators (Prednisolone+ Azathioprine, HD-DXM, and Rituximab) relapsed than those on Romiplostim and Eltrombopag (81.9%, 70.8%, and 70.7% vs. 49.3%, and 44.7%, respectively; p-value < 0.01). We also describe 23 reports of pulmonary hypertension with Prednisolone+ Azathioprine and 13 reports with HD-DXM. The thrombotic events occurred in 16.6% and 13% of patients who received Eltrombopag and Romiplostim treatment, respectively. Most patients had at least one or two risk factors (92.8% of cases). Corticosteroids are effective first-line therapy in primary ITP patients. However, relapse is frequent. Eltrombopag and Romiplostim are safer and more effective than Prednisolone, HD-DXM, and Rituximab. They might be reasonable beneficial options after a one-month HD-DXM regimen.